Juridical Analysis of the Use of Barcodes in Notarial Deeds in Order to Improve Security Aspects - Riqoyani, Kharisma Adelia (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to determine and examine the position of notarial deeds in relation to the use of barcodes in order to improve security aspects, and to determine and examine the legal consequences of the use of notarial deed barcodes in order to improve security aspects. The research approach method is normative juridical. The research specifications are descriptive analytical. Data sources consist of primary data, secondary data in the form of primary legal materials and secondary legal materials, and tertiary data. Data collection techniques are in the form of literature studies using library research techniques. Then all data is analyzed using qualitative descriptive methods. The results of the study indicate that the legal analysis of the use of barcodes in notarial deeds in order to improve security aspects: First, the position of notarial deeds in relation to the use of barcodes in order to improve security aspects is that as long as notarial deeds that use barcodes do not change, replace, and do not add words that can lead to other interpretations with the substance of the head of the deed, the contents of the deed, and the closing of the deed, it means that it is valid. Second, the legal consequences of the use of barcodes in notarial deeds in order to improve security aspects are that there are no prohibitions, so that the purpose of securing notarial deeds can be carried out properly and correctly as long as they do not conflict with the UUJN.Keywords: Barcode; Deed; Security.